Echocardiographic Determination of Resting Hemodynamics and Optimal Positioning in Term Pregnant Women. Issue 3 (September 2019) - Dennis, A.T.; Buckley, A.; Mahendrayogam, T.; Castro, J.M.; Leeton, L.
Abstract : ( Anaesthesia . 2018;73:1345–1352) In pregnant women undergoing anesthesia, positioning is important for minimizing the risk of airway trauma or failed tracheal intubation as well as preventing aortocaval compression and reduced cardiac output. These 2 goals are achieved through 2 different positions: the head elevated ramped position for tracheal intubation and left lateral pelvic tilt for prevention of aortocaval compression. There have been no studies examining the hemodynamic effects of combining these 2 positions in parturients. This study aimed to determine whether there was any significant difference in maternal cardiac output between the ramped position combined with left lateral pelvic tilt compared with the ramped position alone determined by calculations based on transthoracic echocardiographic measurements.